Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Struktur Modal pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (Universitas Muhammadiyah Palembang, 2022)
This study aims to determine the effect of profitability, liquidity, and firm size on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange (IDX). The type of research used is descriptive research and associative research. The data used in this study is secondary data obtained from the IDX official website (www.idx.co.id). Methods of data collection using the method of documentation. The data analysis used is quantitative analysis. The analysis technique is multiple linear regression analysis with the help of the Eviews version 20 application. The results of the study together that the variables of profitability, liquidity, and company size have a significant positive effect on the capital structure of food and beverage companies on the Indonesia Stock Exchange. Profitability has a significant effect on capital structure, liquidity has a significant effect on capital structure, while firm size has not a significant effect on capital structure.